2010
DOI: 10.1007/s10681-010-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of tomato SSR markers from genomic sequences of anchored BAC clones on chromosome 6

Abstract: Simple sequence repeat motifs are abundant in plant genomes and are commonly used molecular markers in plant breeding. In tomato, currently available genetic maps possess a limited number of simple sequence repeat (SSR) markers that are not evenly distributed in the genome. This situation warrants the need for more SSRs in genomic regions lacking adequate markers. The objective of the study was to develop SSR markers pertaining to chromosome 6 from bacterial artificial chromosome (BAC) sequences available at S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
(56 reference statements)
1
20
1
Order By: Relevance
“…He et al (2003) have identified 2.7 alleles per locus on average among 17 varieties and 2 parental lines of tomatoes. We used diverse tomato genetic resources preserved in the National Agrobiodiversity Center (RDA, Republic of Korea) and applied the 18 SSR markers which revealed high alleles and polymorphism based on the previous studies (Kwon et al 2009;Geethanjali et al 2010;Geethanjali et al 2011). These factors might cause relatively high average NA per locus in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He et al (2003) have identified 2.7 alleles per locus on average among 17 varieties and 2 parental lines of tomatoes. We used diverse tomato genetic resources preserved in the National Agrobiodiversity Center (RDA, Republic of Korea) and applied the 18 SSR markers which revealed high alleles and polymorphism based on the previous studies (Kwon et al 2009;Geethanjali et al 2010;Geethanjali et al 2011). These factors might cause relatively high average NA per locus in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of each DNA sample was adjusted to 20 ng/l. For SSR assays, a total of 18 polymorphic SSR markers were selected from SOL Genomics Network (https://solgenomics.net) and those reported previously (Kwon et al 2009;Geethanjali et al 2010;Geethanjali et al 2011). SSR alleles were amplified with fluorescent labelled primers, resolved on ABI Prism 3100 DNA sequencer (Applied Biosystems, Foster City, CA, USA) using GeneScan 3.7 software (Applied Biosystems), and sized precisely using GeneScan 500 ROX (6-carbon-X-rhodamine) molecular size standards (35-500 bp) and Genotyper 3.7 software (Applied Biosystems).…”
Section: Ssr Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…These genotypes represented diverse origins and possessed useful traits such as resistance to biotic and abiotic stresses. More details of the accessions are available in Geethanjali et al (2010). The seeds of these genotypes were obtained from Genetic Resources and Seed Unit, AVRDC-The World Vegetable Center (AVRDC), Taiwan.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%
“…Recently, Ohyama et al (2009) and Shirasawa et al (2010) developed a large number of SSR markers using bacterial artificial chromosome (BAC)-ends, cDNA and EST sequences from genome databases. Geethanjali et al (2010) developed a total of 54 SSR markers from 17 complete BAC clone sequences on chromosome 6 and mapped 21 of them. Currently, a total of 1707 tomato SSR markers have been mapped; 1686 of them in high density linkage map derived from S. lycopersicum 9 S. pennellii cross and 21 of them in the linkage map derived from West Virginia 700 (S. pimpinellifolium) and Hawaii 7996 (S. lycopersicum) cross.…”
Section: Introductionmentioning
confidence: 99%